Early Infarct Growth Rate Correlation With Endovascular Thrombectomy Clinical Outcomes: Analysis From the SELECT Study. Issue 1 (January 2021) - Sarraj, Amrou; Hassan, Ameer E.; Grotta, James; Blackburn, Spiros; Day, Arthur; Abraham, Michael; Sitton, Clark; Dannenbaum, Mark; Cai, Chunyan; Pujara, Deep; Hicks, William; Vora, Nirav; et al.
Abstract : Background and Purpose: Time elapsed from last-known well (LKW) and baseline imaging results are influential on endovascular thrombectomy (EVT) outcomes. Methods: In a prospective multicenter cohort study of imaging selection for endovascular thrombectomy (SELECT [Optimizing Patient's Selection for Endovascular Treatment in Acute Ischemic Stroke], the early infarct growth rate (EIGR) was defined as ischemic core volume on perfusion imaging (relative cerebral blood flow<30%) divided by the time from LKW to imaging. The optimal EIGR cutoff was identified by maximizing the sum of the sensitivity and specificity to correlate best with favorable outcome and to improve its the predictability. Patients were stratified into slow progressors if EIGR<cutoff and fast progressors if EIGR≥the optimal cutoff. Good collaterals were defined on computed tomography perfusion as a hypoperfusion intensity ratio <0.4 and on computed tomography angiography as collateral score >2. The primary outcome was 90-day functional independence (modified Rankin Scale score =0–2). Results: Of 445 consented, 361 (285 EVT, 76 medical management only) patients met the study inclusion criteria. The optimal EIGR was <10 mL/h; 200 EVT patients were slow and 85 fast progressors. Fast progressors had a higher median National Institutes of Health Stroke Scale (19 versus 15, P <0.001), shorter time from LKW to groin puncture (180 versus 266 minutes, P <0.001). Slow progressors had better collaterals on computed tomography perfusion: hypoperfusion intensity ratio (adjusted odds ratio [aOR]: 5.11 [2.43–10.76], P <0.001) and computed tomography angiography: collaterals-score (aOR: 4.43 [1.83–10.73], P =0.001). EIGR independently correlated with functional independence after EVT, adjusting for age, National Institutes of Health Stroke Scale, time LKW to groin puncture, reperfusion (modified Thrombolysis in Cerebral Infarction score of ≥2b), IV-tPA (intravenous tissue-type plasminogen activator), and transfer status (aOR: 0.78 [0.65–0.94], P =0.01). Slow progressors had higher functional independence rates (121 [61%] versus 30 [35%], P <0.001) and had 3.5 times the likelihood of achieving modified Rankin Scale score =0–2 with EVT (aOR=2.94 [95% CI, 1.53–5.61], P =0.001) as compared to fast progressors, who had substantially worse clinical outcomes both in early and late time window. The odds of good outcome decreased by 14% for each 5 mL/h increase in EIGR (aOR, 0.87 [0.80–0.94], P <0.001) and declined more rapidly in fast progressors. Conclusions: The EIGR strongly correlates with both collateral status and clinical outcomes after EVT. Fast progressors demonstrated worse outcomes when receiving EVT beyond 6 hours of stroke onset as compared to those who received EVT within 6 hours. Registration: URL: https://clinicaltrials.gov . Unique identifier: NCT02446587. Abstract : Supplemental Digital Content is available in the text.